HELP! Calcul littéral

Factoriser:
K=(3x+2)² - (3x+2)(x+7)

L= (5x+3)² - (5x+3)(2x-4)

M=(3x+2)(4x+1) - (4x+1)²

N= (x+3)² + (x+3)

Merci de ne pas mettre de réponses inutile ,sinon je vous signal. Merci :)

1

Réponses

2013-12-01T16:40:24+01:00
K = (3x+2)²-(3x+2)(x+7)
   =(3x+2)(3x+2)-(x+7)
   =(3x+2)(3x+2-x-7)
   =(3x+2)(2x-5)
L = (5x+3)²-(5x+3)(2x-4)
   =(5x+3)(5x+3)-(2x-4)
   =(5x+3)(5x+3-2x+4)
   =(5x+3)(3x+7)
M = (3x+2)(4x+1)-(4x+1)²
   =(4x+1)(3x+2)-(4x+1)
   =(4x+1)(3x+2-4x-1)
   =(4x+1)(-x+1)
N = (x+3)²+(x+3)
   =(x+3)(x+3)+1
  =(x+3)(x+4)
K=(3x+2) ((3x+2) - (x+7))
K=(3x+2) (3x+2-x-7)
K=(3x+2) (2x-5)

L=(5x+3) ((5x+3) - (2x-4))
L=(5x+3) (5x+3-2x+4)
L=(5x+3) (3x+7)

M=(4x+1) ((3x+2) - (4x+1))
M=(4x+1) (3x+2-4x-1)
M=(4x+1) (-x-1)

N=(x+3) ((x+3) + 1)
N=(x+3) (x+3+1)
N=(x+3) (x+4)
Une autre façon ci-dessus :
merciii:)